2017
DOI: 10.3390/ma10091000
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heat Treatment on the Emission Color of P-Doped Ca2SiO4 Phosphor

Abstract: In a series of (Ca2–x/2–yEuy□x/2)(Si1–xPx)O4 (x = 0.06, 0.02 ≤ y ≤0.5), various color-emitting phosphors were successfully synthesized by a solid-state reaction. These phosphors were characterized by photoluminescence (PL) spectroscopy, X-ray powder diffractometry, transmission electron microscopy, and X-ray absorption fine structure spectroscopy. We evaluated the effect of heat treatment on PL properties with various annealing temperatures at 1373–1773 K for 4 h before/after reduction treatment from Eu3+ to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…With increasing relative amount of the IC-phase with respect to the coexisting β-phase (Table 1), the PL intensity of the phosphor steadily decreased to reach the minimum, at which the specimen was composed exclusively of the IC-phase. As reported previously [8], the PL intensity has also been related to the relative amount of the α' L phase with respect to the β phase.…”
Section: Constituent Phases and Crystal Structure Of Ic-phasesupporting
confidence: 60%
See 1 more Smart Citation
“…With increasing relative amount of the IC-phase with respect to the coexisting β-phase (Table 1), the PL intensity of the phosphor steadily decreased to reach the minimum, at which the specimen was composed exclusively of the IC-phase. As reported previously [8], the PL intensity has also been related to the relative amount of the α' L phase with respect to the β phase.…”
Section: Constituent Phases and Crystal Structure Of Ic-phasesupporting
confidence: 60%
“…Rare-earth doped dicalcium silicate (Ca 2 SiO 4 , C 2 S) polymorphs have been the subject of extensive study because of the promising applicability of stabilized high-temperature modifications to the phosphor materials of white light-emitting LEDs [1][2][3][4][5][6][7][8]. The red light emission is characteristic of the Eu 3+ -activated phosphors, due to the transition of the 5 D 0 -7 F 2 for Eu 3+ ion [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nakano et al have reported the effect of annealing temperature on the photoluminescence of Eu doped Ca 2 SiO 4 . They observed a red emission at 1773 K and green emission at 1473 K [ 14 ]. Recently, a significant work on Eu/Nd-doped Ca 12 Al 14 O 33 and CaAl 2 O 4 phosphors as long-lasting blue emitters has also been carried out [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optical properties of the materials also play a crucial role in several applications, like optoelectronics, integrated optics, solar power engineering and optical sensor technology. Generally, compounds like C 2 S, Ca 2 SiO 4 and CaAl 2 O 4 are considered as standard phosphor materials [12][13][14][15]. It is reported that doping of P ions in the green emitting C 2 S:Eu 2+ effectively enhances the PL intensities [13].…”
Section: Introductionmentioning
confidence: 99%
“…From the slopes of the ln[I0/I(T) − 1] versus 1/kT plots (Figure 5b,d), which were well fitted to Equation (3), the ΔEs were determined as 0.21 and 0.26 eV under excitation at 289 and 365 nm, respectively. Table 1 compares the CIE chromaticity coordinates, CCT and lifetimes of Na2YMg2V3O12:0.03Dy 3+ , and other Dy 3+ -doped phosphors [39][40][41]. The obtained Na2YMg2V3O12:Dy 3+ phosphors presented relatively high thermal stability and are potentially applicable to WLEDs.…”
Section: Resultsmentioning
confidence: 99%